PENGARUH LATIHAN NAIK TURUN TANGGA TERHADAP LOMPAT JAUH SISWA KELAS VIII SMPN 17 KENDARI - Irfan; Saifu; Suhartiwi (Journal Olympic (Physical Education, Health and Sport), 2021)
The purpose of this study was to determine the effect of up and down stairs training on the long jump ability of the eighth grade students of SMPN 17 Kendari. The method in this study is classified in the form of experimental research with a research design using a one-group pretest-posttest design model. The variables in this study consisted of independent variables, namely up and down stairs training and the dependent variable, namely the long jump ability. The population in this study were all students of class VIII SMPN 17 Kendari totaling 221 students consisting of 120 male students and 101 female students. The sampling technique was carried out using purposive sampling by taking a sample of 25% of 120 male students in order to obtain a sample of 30 people. The data analysis technique used t-test with the help of SPSS 20 by fulfilling the normality and homogeneity requirements. The results of this study by analyzing the t-test between the pre-test and post-test results of the long jump results of class VIII students at SMPN 17 Kendari obtained t-count 14.063 and a significance of 0.000. This statistical result shows that between the pre-test and post-test has increased. This research can be concluded that there is an effect of training up and down stairs on the long jump ability of the eighth grade students of SMPN 17 Kendari.